2022
DOI: 10.18196/di.v11i2.16077
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Medical Record Document Filling Completeness of Outpatient at Nala Husada Dental Hospital

Abstract: Medical records (RM) as patient health information recorded assessment results, plans and implementation of care, treatment, integrated patient progress, as well as a summary of discharge for inpatients made by PPA. The results of medical record documents tracing at the Nala Husada dental hospital found that the RM was incomplete. This study aims to analyze the completeness of medical records filling that does not align with the accreditation standard of medical records management and health information (MRMIK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…The results of the study related to the frequency of incomplete filling of important reporting showed results that were in line with Indarti and Agustia's research 15 showing that the results of a quantitative analysis of important reporting of medical record documents at RSGM Nala Husada were 84% complete and 16% incomplete. Other supporting research, namely research by Yanti and Yulianti 16 showed that the completeness of filling in the summary form of entry and exit on the patient reporting component of cases of the Internal Medicine Polyclinic had not been completed, namely the disease diagnosis item, disease code, disease history, date of admission, condition out, the action taken and the action code where the incomplete percentage of each item is 16% incomplete and 84% complete.…”
Section: Discussionsupporting
confidence: 83%
“…The results of the study related to the frequency of incomplete filling of important reporting showed results that were in line with Indarti and Agustia's research 15 showing that the results of a quantitative analysis of important reporting of medical record documents at RSGM Nala Husada were 84% complete and 16% incomplete. Other supporting research, namely research by Yanti and Yulianti 16 showed that the completeness of filling in the summary form of entry and exit on the patient reporting component of cases of the Internal Medicine Polyclinic had not been completed, namely the disease diagnosis item, disease code, disease history, date of admission, condition out, the action taken and the action code where the incomplete percentage of each item is 16% incomplete and 84% complete.…”
Section: Discussionsupporting
confidence: 83%